Mental modeling approach : risk management application case studies - Wood, Matthew D. (Risk, systems and decisions (Series), 2017)
This book provides an easy-to-read, user-oriented introduction to mental models research and Mental Modeling TechnologyTM. Mental models are powerful influences human behavior. The book offers insight from the developers and most experienced application professionals of a widely proven methodology for understanding and influencing human judgment, decision making and behavior. The case studies show examples of the methodological concepts in their application context. It is one of the most comprehensive collections of cases focused on government needs of any similar qualitative analysis approach. Finally, it presents an introduction to software tools and tutorials that enable readers to use the approach for their own research needs.- Resumé vydavatel